use of AR to preserve and popularize traditional Chinese musical instruments as part of the formation of the tourist attractiveness of the national art of Guizhou province. - Hong, Xin; Wu, Yuan-Hua (Digital Scholarship in the Humanities, 2022)
This article explores augmented reality (AR) possibilities for the preservation of national cultural art, popularization of Chinese musical instruments among the youth, and meeting the tourist interest in the cultural heritage of China in a fascinating interactive form. Using the generated database containing information on traditional musical instruments of the Guizhou province, the authors have developed an AR application adapted for educational and tourist purposes. Its central aim was to acquaint people with traditional Chinese musical instruments in the context of familiarization with the national culture of China. Testing of the developed application was carried out by hundred students from Guizhou Minzu University (College of Tourism and Steward, the College of Media, the College of Music and Dance, and the College of Data Science and Information Engineering) as part of the National Culture and Art study course. As a result, the created AR app was proved to expand the understanding of the culture and traditions of the Chinese people, intensify the perception of national musical identity, increase interactivity-caused inspiration and involvement (89%), and enhance interest in new knowledge (93%). Based on the obtained research outcomes, a model for the popularization of traditional Chinese musical instruments in the structure of the integrated national tourism product of Guizhou province was developed. The article is believed to be useful for individuals studying the national cultural heritage of China and educators seeking innovative solutions that improve the educational practice.